Reproductive Performance of Crossbreed Goats Etawah in Kulon Progo Regency - Triswanto Triswanto; Nono Ngadiyono; Sumadi Sumadi (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2019)
The purpose of this research is to know the effect of age on reproductive performance of Crossbreed goat etawah in Kulon Progo regency in a productive age. The object of this research is the respondents and their Goats as the research material that is the Doe Crossbreed goat Etawah which is 1.5 until 3 years old (poel 2 to 3 pairs). The method used in this research is a survey through an interview using a questionnaire. Location is determined by population level that is population high, middle and low in Sub Girimulyo and Samigaluh. The observed reproduction performance was litter size, postpartum estrus, postpartum mating, service per conception and lambing interval. The research data is conducted by Independent T-test. The results showed that the litter size, postpartum estrus, postpartum mating, service per conception and lambing interval were not significantly different between the age of poel 2 and poel 3. The litter size poel 2 and 3 were 1.65+0, 54 and 1.72±0.55. Postpartum estrus goat poel 2 is 4.37±1.23 and goat poel 3 is 4.46±1.19. Postpartum mating goats poel 2 and 3 are 4.38±1.23 and 4.46±1.19. The number of lambing intervals of crossbreed goat etawah poel 2 and 3 respectively were 9.54±1.35 and 9.60±1.28. Service per conception of crossbreed goat etawah poel 2 equal to 1.28±0.65, poel 3 equal to 1.22±0.55. It can be concluded that the reproductive performance of crossbreed goat etawah at the productive age of 1.5 to 3 years is not affected by age.